Clinical Application of Development of Nonantibiotic Macrolides That Correct Inflammation-Driven Immune Dysfunction in Inflammatory Skin Diseases - Carmen Rodriguez-Cerdeira; Elena Sanchez-Blanco; Alberto Molares-Vila (Hindawi Limited, 2012)
Background. Inflammation-driven immune dysfunction supports the development of several chronic human disorders including skin diseases. Nonantibiotic macrolides have anti-inflammatory and/or immunomodulatory activity that suggests the exploitation of these in the treatment of skin diseases characterized by inflammatory disorders. Materials and Methods. We performed an extensive review of the nonantibiotic macrolide literature published between 2005 and 2012, including cross-references of any retrieved articles. We also included some data from our own experience. Results. Calcineurin antagonists such as tacrolimus and ascomycins (e.g., pimecrolimus) act by inhibiting the activation of the nuclear factor for activated T cells (NFAT). There are new applications for these macrolides that have been available for several years and have been applied to skin and hair disorders such as atopic dermatitis, oral lichen planus, vitiligo, chronic autoimmune urticaria, rosacea, alopecia areata, pyoderma gangrenosum, Behcet's disease, neutrophilic dermatosis, and lupus erythematosus. We also reviewed new macrolides, like rapamycin, everolimus, and temsirolimus. In addition to the literature review, we report a novel class of nonantibiotic 14-member macrocycle with anti-inflammatory and immunomodulatory effects. Conclusions. This paper summarizes the most important clinical studies and case reports dealing with the potential benefits of nonantibiotic macrolides which have opened new avenues in the development of anti-inflammatory strategies in the treatment of cutaneous disorders.